Nurses´ knowledge of enteral nutrition for the critically ill adults: a diagnostic study - Joaquim, Rui; Costeira, Cristina (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: The critically ill person has significant metabolic changes associated with the severity of the illness, which result in increased nutritional requirements and disturbed homeostasis due to increased protein and calorific metabolism. Nurses, who play an important role in the administration of Enteral Nutrition (EN), must have specific knowledge to ensure safe, quality care with health gains and cost savings. Objective: To assess nurses' level of knowledge about enteral nutrition in the critically ill and to identify the influence of sociodemographic and professional characteristics on this knowledge. Methods: A diagnostic study with a quantitative approach was conducted among nurses working in a cardiac specialty intensive care unit at a Local Health Unit in Portugal. Data were collected through an electronic questionnaire and analysed using statistical software. Results: 36 nurses took part, with a mean age of 42.72±10.70 years. The majority did not hold a nursing specialist qualification (66.7%) and 77.8% reported a perception of insufficient knowledge about NS. The average number of correct answers was 26.5±6.07 (out of 43), with statistically significant differences (p<0.05) in the number of correct answers according to the age of the nurses and whether they held a nursing specialist qualification. Conclusion: The level of knowledge proved to be inadequate, which is why the implementation of a training programme in the field of NE will be relevant to expanding knowledge and providing appropriate nutritional management, improving clinical practice and ensuring the provision of safe care.